Patient, caregiving partner, and clinician recommendations for improving heart failure care in the Veterans Health Administration. (June 2022) - Slightam, Cindie; Risbud, Rashmi; Guetterman, Timothy C; Nevedal, Andrea L; Nelson, Karin M; Piette, John D; Trivedi, Ranak B
Objective: Heart Failure (HF) care requires substantial care coordination between patients, patients' informal caregivers, and clinicians, but few studies have examined recommendations from all three perspectives. The objective of this study was to understand and identify shared recommendations to improve HF self-care from the perspective of VA persons with HF, their caregiving partners, and clinicians. Methods: Secondary data analysis from a study of semi-structured interviews with 16 couples (persons with HF and their caregiving partners) and 13 clinicians (physicians, nurses, other specialists) from a large Veterans Affairs (VA) hospital. Interviews were double-coded, and analyzed for themes around commonly used or recommended self-care strategies. Results: Three themes emerged: (1) Couples and clinicians believe that improvements are still needed to existing HF education, especially the need to be tailored to learning style and culture, (2) Couples and clinicians believe that technology can facilitate better HF self-care, and (3) Couples and clinicians believe that caregiving partners are part of the self-care team, and should be involved in care management to support the person with HF. Discussion: Recommendations from couples and clinicians address barriers to HF self-care and encourage patient-centered care.